2008
DOI: 10.1016/j.ijid.2007.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute acalculous cholecystitis during the course of primary Epstein–Barr virus infection: a new case and a review of the literature

Abstract: Acute acalculous cholecystitis may occur during the course of acute EBV infection, especially in patients with cholestatic hepatitis. Clinicians should be aware of the possible involvement of the gallbladder during EBV infection to avoid unnecessary invasive procedures or the overuse of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 22 publications
4
63
0
5
Order By: Relevance
“…Some reports have described AAC following systemic diseases, including systemic lupus erythematosus, nephrotic syndrome, and Kawasaki disease (4,5). AAC associated with EBV infection has also been reported, but as far as we know, only eight child patients, including the present case, have been described (6,7).…”
Section: Discussionmentioning
confidence: 68%
“…Some reports have described AAC following systemic diseases, including systemic lupus erythematosus, nephrotic syndrome, and Kawasaki disease (4,5). AAC associated with EBV infection has also been reported, but as far as we know, only eight child patients, including the present case, have been described (6,7).…”
Section: Discussionmentioning
confidence: 68%
“…Literatürde bildirilen vakalarda kolestatik hepatit ve kolesistit birlikteliği saptanmış ve akut kolesistitin safra stazı ya da safra kesesinin virüs tarafından direkt invazyonuna bağlı olarak geliştiği düşünülmüştür. (10,11,12,13,14). Akut kolesistit tanısında ultrasonografi en yararlı incelemedir.…”
Section: Discussionunclassified
“…Safra kesesi duvarı kalınlığında artış (≥3,5mm) tanısal kabul edilmektedir. Diğer tanıya yardımcı ultrasonografi bulguları perikolesistik sıvı, intramural gaz ve sonolüsen halo varlığıdır (12,13). Kolestatik hepatitin eşlik ettiği kolesisti olan hastamızda ultrasonografik inceleme ile safra kesesi duvarında kalınlaşma ve ödem ve bunların yanı sıra asit gözlenmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…These complications occur in 6% to 82% of cases. 3,7,8 Most studies had revealed high mortality rate associated with AAC ( 10%-90% with early or late diagnosis, respectively 3,5,8,9 ). The etiology of AAC is multifactorial and likely results from bile stasis or ischemia or both.…”
Section: 5mentioning
confidence: 99%